The methyl jasmonate-responsive transcription factor DobHLH4 promotes DoTPS10, which is involved in linalool biosynthesis in Dendrobium officinale during floral development - Yu, Zhenming (Plant science : an international journal of experimental plant biology, 2021)
Copyright © 2021 Elsevier B.V. All rights reserved.